Sensorless vector control of a permanent magnet synchronuous motor with fuzzy logic observer - Gumus, Bilal; Ozdemir, Mehmet (Springer, 2006)
In this paper, a new method for sensorless vector control of a permanent magnet synchronous motor (PMSM) using a fuzzy logic observer is developed. This method is based on determination of rotor position and thereby speeds by estimating back-emf components which result from fuzzy logic observers. The rotor position angle and rotating speed are estimated by evaluating the instantaneous values of stator voltages and currents. The estimators are two fuzzy logic observers. They have two inputs: the estimated stator currents and the difference between the measured and estimated stator currents. In addition, the outputs of the fuzzy logic observers are the back-emf components in an alpha-beta reference frame. The proposed method was implemented using a MATLAB/Simulink software package program. The obtained results are within acceptable error limits for a wide speed range, from 40 rad/s up to 500 rad/s.
Keywords: permanent magnet synchronous motor; sensorless control; fuzzy logic observer